Сократите дробь √3-3 в знаменателе 3√2-√6

danilshcherbin danilshcherbin    2   30.06.2019 21:30    2

Ответы
swdw1 swdw1  02.10.2020 16:38
1)  ( √ 3 ) - 3 = √ 3 * ( 1 - √ 3 ) 
2) ( 3 √ 2 ) - ( √ 6 ) = ( 3 √ 2 ) - ( √ ( 3 * 2 ) ) = √ 2 * ( 3 - ( √ 3 )) = 
= ( √ 2 ) * ( √ 3 ) * ( √ 3 - 1 ) = - ( √ 6 ) * ( 1 - √ 3 )
3)  cокращаем числитель и знаменатель на ( 1 - √ 3 )
4) получаем 
   ( √ 3 ) : ( - √ 6 ) = - √ ( 3/6 ) = - √ ( 1/2 ) = - √ 0,5 
ответ минус √ 0,5
ПОКАЗАТЬ ОТВЕТЫ
ketiler13 ketiler13  02.10.2020 16:38
√3-3/3√2-√6 = -(3-√3)/√2(3-√3) = -1/√2=-√2/2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра